MALAYSIA'S RESPONSE IN DEALING WITH REFUGEES: HAS IT BEEN ENOUGH TO PROTECT CITIZENS? - Zuraini Ab Hamid; Muammar Kamil Abd Mohsin; Shukriah Mohd Sheriff, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Due to sovereignty, security, and economic concerns, Malaysia has neither become a state party to any United Nations Protocol Relating to Refugees nor developed integrated national legislation for refugees. Therefore, this has led to the informal acknowledgement of the refugees' status as 'illegal migrants' in Malaysia. As illegal migrants, they are subjected to legal and social persecution, hence the negative connotations they have in society and the host country. Today, the increasing number of refugees fleeing to Malaysia has become a concern towards the country's interest of its citizen's safety and its value as a tourist destination. In addition, many believe that the Malaysian government is inept in handling and controlling the sudden influx of refugees, affecting citizens' rights. This discomfort has led the government to be criticised for dismissing the citizen's rights in favour of the refugees. Residents also believe the Malaysian government has jeopardised citizens' rights to a safe environment and decent income. As a result, they demand that the government prioritise citizens' rights over refugees' rights. This paper examines the effectiveness of Malaysia's response to the issue of refugees and the protection of its citizen's rights. In the presence of comprehensive efforts by the Malaysian government, this paper further recommends some appropriate measures to balance the rights of refugees and its citizen.